2001
DOI: 10.4049/jimmunol.167.6.3190
|View full text |Cite
|
Sign up to set email alerts
|

CD19 Can Regulate B Lymphocyte Signal Transduction Independent of Complement Activation

Abstract: B lymphocytes are critically regulated by signals transduced through the CD19-CD21 cell surface receptor complex, where complement C3d binding to CD21 supplies an already characterized ligand. To determine the extent that CD19 function is controlled by complement activation, CD19-deficient mice (that are hyporesponsive to transmembrane signals) and mice overexpressing CD19 (that are hyperresponsive) were crossed with CD21- and C3-deficient mice. Cell surface CD19 and CD21 expression were significantly affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 71 publications
(61 reference statements)
5
32
1
1
Order By: Relevance
“…Furthermore, despite peripheral B cells in the C3 −/− hCR2 high mice having equivalent surface IgM levels they displayed a 3 fold increase in hCR2, a 1.5 fold increase in mCR1/2 and a significant increase in CD19 expression levels when compared to B cells isolated from mice which expressed normal levels of C3 ( Figure 5B-F). In the case of mCR1/2 and CD19, these data are in complete agreement with those previously reported on the C3 −/− background (Hasegawa et al, 2001). Thus, the increase in hCR2 expression levels in C3 −/− background suggests that it has been integrated into the mechanisms that modulate the expression levels of endogenous co-receptor proteins on the B cell surface.…”
Section: Absence Of C3 Results In a 3 Fold Increase In B Cell Expresssupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, despite peripheral B cells in the C3 −/− hCR2 high mice having equivalent surface IgM levels they displayed a 3 fold increase in hCR2, a 1.5 fold increase in mCR1/2 and a significant increase in CD19 expression levels when compared to B cells isolated from mice which expressed normal levels of C3 ( Figure 5B-F). In the case of mCR1/2 and CD19, these data are in complete agreement with those previously reported on the C3 −/− background (Hasegawa et al, 2001). Thus, the increase in hCR2 expression levels in C3 −/− background suggests that it has been integrated into the mechanisms that modulate the expression levels of endogenous co-receptor proteins on the B cell surface.…”
Section: Absence Of C3 Results In a 3 Fold Increase In B Cell Expresssupporting
confidence: 92%
“…The fact that addition of C3 containing sera can result in rapid down regulation of members of the CR2/ CD19 signaling complex suggests that tight regulation or feedback on expression levels of these molecules exist. This data fits with the idea that a common regulatory loop exists between C3, CR1/2 and CD19 that influences B cell signaling thresholds as suggested by Tedder and colleagues (Hasegawa et al, 2001). Our bone marrow data demonstrates the regulation of hCR2 expression levels in the presence of C3 is at the transition between B220 lo and B220 hi status and thus, is likely to be concurrent with the expression of sIgM or pre-BCR.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was also reported that IgM and heparan sulfate binds to CD19 as complement-independent ligands. 8,9 CD19 has also been implicated as a signaling partner for several other surface receptors including CD40, 10 CD38, 11 CD72, 10 VLA4 12 and Fc␥RIIB. 13,14 Altering CD19 density on the cell surface in gene-targeted or transgenic mice has been shown to significantly influence B cell functions.…”
Section: Introductionmentioning
confidence: 99%